Elucidation of the Formation Mechanism of Metal-Organic Frameworks via in-Situ Raman and FTIR Spectroscopy under Solvothermal Conditions - Embrechts, Heidemarie; Kriesten, Martin; Hoffmann, Kilian; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (Journal of Physical Chemistry C, 2018)
The metal–organic framework MIL-53(Al) serves as a model system in this study. Its formation mechanism in N,N-dimethylformamide (DMF) is elucidated through simultaneous FTIR and Raman spectroscopy and turbidity measurements collected under in-situ synthesis conditions in a custom-designed solvothermal reactor coupled with reaction sampling. Different synthesis steps are followed over synthesis time including a prenucleation building unit (PNBU) consisting of one linker molecule and one aluminum atom, the assembly of the PNBUs to MIL-53 nuclei in solution, the decomposition of DMF to formic acid and dimethylammonium, and finally the precipitation of the crystalline MOF phase. The rearrangement of the PNBU to form MIL-53 is identified as the rate-limiting reaction step responsible for the long induction time at low temperatures (<80 °C). MOF nucleation and particle growth is followed directly in-situ through a novel method—comparison of the temporal evolution of the respective FTIR and Raman bands. Analysis of the particles isolated after various synthesis times indicates that MIL-53(H2BDC) of low crystalline long-range order is formed initially, which quickly rearranges to form more ordered, crystalline particles with DMF inside of the pores (MIL-53(DMF)). It is to be expected that the synthesis steps elucidated herein can be generalized to the solvothermal synthesis of other metal–organic framework structures from metal salts and organic acid li
Keywords: Organic acids; Fourier transform infrared spectroscopy; Chemical synthesis; Metal organic frameworks; Raman spectroscopy; Bis(1; 3; 5-Benzenetricarboxylate)Tricopper(Ii); MIL-101; Metalorganic Framework; Crystalline materials; Dimethylformamide; Metals: Organic polymers; Organic solvents; Organometallics; Synthesis (chemical); Crystalline particles; Formation mechanism; Metal organic framework; N; N-Dimethylformamide; Rate-limiting reaction; Solvothermal conditions; Solvothermal synthesis; Turbidity measurements